EXPERIMENTAL AND INNOVATIVE ACTIVITIES IN THE FIELD OF EDUCATION (International journal of artificial intelligence, 2024)
This emphasizes the importance of leveraging cutting-edge, modern, experimental, and innovative technologies and methodologies to empower students and young people. By employing these crucial tools, individuals can easily tackle various challenges, foster their creativity, enhance critical thinking skills, and embark on research journeys within their respective fields. It underscores the significance of utilizing these resources in a strategic and thoughtful manner, taking into consideration all relevant factors and ensuring that they are positioned effectively to maximize their impact.